Approach To Islamic Values In Guidance And Counseling Services For Students Who Are Indicated To Have Borderline Personality Disorder - Ibadullah, Hafiz Hasbi; Kusnawan, Aep; Fajar, Dadang Ahmad (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
The research was inspired by the discovery of BPD disorder in a female student and observed the positive impact of guidance and counseling services by guidance and counseling teachers. The aim of the research is to evaluate the planning, implementation and impact of counseling guidance services on students with indications of BPD. The evaluation model used is goal free evaluation, which focuses on the impact of activities rather than specific goals. The chosen approach is qualitative with descriptive methods to produce a clear explanation of the findings. The research results show that counseling guidance services can be applied eclectically, combining various approaches and methods, so that they are more effective for students with BPD.